2021
DOI: 10.3390/coatings11101208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gd2Zr2O7 Coatings Using the Novel Reactive PS-PVD Process

Abstract: Ceramic topcoats of thermal barrier coatings (TBCs) make it possible to increase the working temperature of the hot sections of jet engines. Yttria-stabilized zirconia oxide (YSZ) is usually used to protect the turbine blades and vanes against high temperature and oxidation. It is necessary to develop new materials which can operate at higher temperatures in a highly oxidizing gas atmosphere. Re2Zr2O7-type pyrochlores are promising YSZ replacements. Usually, they are produced by mixing pure oxides in the calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…They formed as a result of secondary crystallization of material observed when longer spray distance of PS-PVD processes was used [39]. The obtained results of microstructure analysis showed that structure of YZO coating are similar to previously synthetized gadolinium zirconate coating [32].…”
Section: The Microstructuresupporting
confidence: 69%
See 2 more Smart Citations
“…They formed as a result of secondary crystallization of material observed when longer spray distance of PS-PVD processes was used [39]. The obtained results of microstructure analysis showed that structure of YZO coating are similar to previously synthetized gadolinium zirconate coating [32].…”
Section: The Microstructuresupporting
confidence: 69%
“…Both the bond-coat and ceramic topcoat were produced using the LPPS-Hybrid system (Oerlikon-Metco, Switzerland) in the Research and Development Laboratory for Aerospace Materials at Rzeszow University of Technology, Poland. The basic process parameters of the topcoat production were selected based on our previous research [32][33][34][35][36]. The experimental process parameters are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the maximum content of total sulfur in fuels for turbine Additionally, it has been observed that the coating covering the blade's leading edge consists of two layers: an external layer responsible for thermal resistance having an aluminum content of approximately 29% and a thickness of about 40 µm and an inner layer responsible for transferring strain containing approximately 24% Al and having a thickness of about 50 µm. The increased content of aluminum within the zone that is expected to be exposed to the highest temperatures is supposed to facilitate the formation of protective aluminum or chromium oxide layers that are created during engine operation [41,42]. Al 2 O 3 and Cr 2 O 3 [43] form as a result of oxygen diffusion into the coating as well as the core diffusion of aluminum and chromium.…”
Section: Results Of the Metallographic Examination Of The Blade Leadi...mentioning
confidence: 99%
“…Typically for conventional fuel gas turbines the thermal barrier coatings are used for protection of Nickel-superalloys surface material (Grilli et al, 2021;Suzuki et al, 2022). The outer ceramic layer contains usually yttria stabilized zirconia oxide (YSZ) (Golewski and Sadowski, 2019) or pyrochlores (Pędrak et al, 2021;. The bond coat protects surface against oxidation and hot corrosion and might be formed from MCrAlYtype alloys (Zakeri et al, 2022) or by production of aluminide coatings (Góral et al, 2021;Kopec et al, 2021).…”
Section: Introductionmentioning
confidence: 99%